2020
DOI: 10.5535/arm.2020.44.1.38
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Patients With Esophageal Dysphagia Assessed by Chest X-Ray Imaging After Videofluoroscopic Swallowing Study

Abstract: Objective To evaluate the prevalence rate, types, characteristics, and associated factors of esophageal dysphagia detected on chest X-ray images after videofluoroscopic swallowing study (VFSS).Methods The medical records of 535 adults were reviewed retrospectively. Chest X-ray images taken after barium swallow study were analyzed and presence of any residual barium in the esophagus was considered as esophageal dysphagia. Esophageal dysphagia was classified based on the largest width of barium deposit (mild, &l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
4
1
1
Order By: Relevance
“…In this analysis, the proportion of subjects with esophageal barium greater than 1 cm was 19% of the subjects, which was even higher than the previously reported 7.5% with presence of esophageal barium residue regardless of the size of diameter [6]. The previous study showed significant differences in the age of subjects based on the presence or absence of esophageal barium residues [6]. The average age of the study population in the previous study was 73.5 years, and the age of population in this study was slightly older (mean age was 74.7 years).…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…In this analysis, the proportion of subjects with esophageal barium greater than 1 cm was 19% of the subjects, which was even higher than the previously reported 7.5% with presence of esophageal barium residue regardless of the size of diameter [6]. The previous study showed significant differences in the age of subjects based on the presence or absence of esophageal barium residues [6]. The average age of the study population in the previous study was 73.5 years, and the age of population in this study was slightly older (mean age was 74.7 years).…”
Section: Discussioncontrasting
confidence: 74%
“…Videofluoroscopic swallowing studies (VFSS) are one of the standard tests to evaluate pharyngeal swallowing function. We previously reported 7.5% of the patients undergoing the test showed some degree of esophageal dysphagia [ 6 ]. When barium in the esophagus with a diameter of 2 cm or more was observed after the VFSS test, lung cancer and esophageal cancer were confirmed through esophagogastroduodenoscopy (EGD) or chest computed tomography (CT) scan, and achalasia was confirmed through barium esophagogram [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This examination is usually used for patients who cannot tolerate or cannot undergo gastrointestinal endoscopy. It has the advantages of relative safety, no side effects, and simple operation ( 11 ). Gastroenterography is widely used in clinical diagnosis and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…12 Authors have previously suggested that residual esophageal barium in a chest radiograph routinely taken immediately after VFSS could indicate esophageal dysphagia. 13 Cardiogenic dysphagia can be suspected if there is a history of previous heart disease and if evidence of cardiomegaly is present on the chest radiograph. If esophageal dysphagia is suspected, assessment for abnormalities may be done through esophagogastroduodenoscopy and manometry.…”
Section: 6mentioning
confidence: 99%